PENGEMBANGAN SMART VILLAGE KAKI LANGIT DENGAN PENGOPTIMALAN WEB INTEGRATIF - Edi Iskandar; Sri Redjeki; Dini Fakta Sari (LPPM STMIK El Rahma Yogyakarta, 2020)
Smart Village is a village that has the ability to use Information and Communication Technology systems in developing the potential for both natural and human resources. Smart Village can indirectly improve the economy of a village, this is supported by the ability of a smart village to communicate the potentials of natural resources outside the village, and provide knowledge or understanding in managing village potential by the villagers. The development of the Kaki Langit Tourism Village is to accommodate people who love their village to work together to carry out their respective activities with TOURISM as a binding knot by prioritizing the value of local wisdom, so that the community will be more prosperous. Likewise, the role of information technology is needed in realizing the skyline tourism village as a smart village pioneer. Kaki Langit Smart Village Development with Integrative Web Optimization can manage data related to kaki langit tourism villages, thus helping visitors in choosing the desired tourist attraction, and applications are developed by integrating web and homestay management applications so as to help visitors in choosing homestays and packages the desired tourism.